Interleukin 17 regulates SHP-2 and IL-17RA/STAT-3 dependent Cyr61, IL-23 and GM-CSF expression and RANKL mediated osteoclastogenesis by fibroblast-like synoviocytes in rheumatoid arthritis. (November 2017) - Ganesan, Ramamoorthi; Rasool, Mahaboobkhan
Highlights: IL-17 regulates Cyr61, IL-23 and GM-CSF expression by AA-FLS via STAT-3 signaling. Knockdown of IL-17RA or inhibition of STAT-3 activation abrogated these effects. IL-17 enhanced the expression of IL-17RA and SHP-2 in AA-FLS. IL-17/IL-17RA/STAT-3 signaling cascade is crucial for RANKL production in AA-FLS. This study provides a new insight into the pathogenesis of rheumatoid arthritis. Abstract: Interleukin (IL)-17 predominately produced by the Th17 cells, plays a crucial role in the fibroblast-like synoviocytes (FLS) mediated disease process of rheumatoid arthritis (RA). IL-17 exerts its pathogenic effects in RA-FLS by IL-17/IL-17RA/STAT-3 signaling. Recent studies have shown that RA-FLS produces SHP-2, Cyr61, IL-23, GM-CSF and RANKL which results in worsening of the disease. However, whether IL-17/IL-17RA/STAT-3 signaling regulates SHP-2, Cyr61, IL-23, GM-CSF and RANKL expressions in RA-FLS remains unknown. In this study, IL-17 treatment dramatically induced the production of Cyr61, IL-23 and GM-CSF in FLS isolated from adjuvant induced arthritis (AA) rats. Conversely, IL-17 mediated production of Cyr61, IL-23 and GM-CSF was abrogated by knockdown of IL-17RA using a small interfering RNA or blockade of STAT-3 activation with S3I-201 in AA-FLS. Interestingly, IL-17 treatment noticeably increased the expression of IL-17RA and SHP-2 in AA-FLS. However, silencing of IL-17RA reversed the effect of IL-17 on the expression of IL-17RA and SHP-2 in AA-FLS. In addition, an increased number of TRAP-positive multinucleated cells were observed in a coculture system consisting of IL-17 treated AA-FLS and rat bone marrow derived monocytes/macrophages. Further, mechanistically we found that IL-17 upregulated RANKL expression in AA-FLS that was dependent on the IL-17/IL-17RA/STAT-3 signaling cascade. Knockdown of IL-17RA or inhibition of STAT-3 activation decreased the IL- 17 induced RANKL expression by AA-FLS and their osteoclastogenic potential. Taken together, our findings demonstrate that IL-17 regulates SHP-2 expression and IL-17RA/STAT-3 dependent production of Cyr61, IL-23, GM-CSF and RANKL in AA-FLS and may reveal a new insight into the pathogenesis of RA.